2012
DOI: 10.1264/jsme2.me12032
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Deep-sea Methane Seep Sediments Presented by SSU rRNA Gene Tag Sequencing

Abstract: Microbial community structures in methane seep sediments in the Nankai Trough were analyzed by tag-sequencing analysis for the small subunit (SSU) rRNA gene using a newly developed primer set. The dominant members of Archaea were Deep-sea Hydrothermal Vent Euryarchaeotic Group 6 (DHVEG 6), Marine Group I (MGI) and Deep Sea Archaeal Group (DSAG), and those in Bacteria were Alpha-, Gamma-, Delta- and Epsilonproteobacteria, Chloroflexi, Bacteroidetes, Planctomycetes and Acidobacteria. Diversity and richness were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 39 publications
0
80
0
Order By: Relevance
“…Our RNA-based molecular ecological study demonstrated that the deeper sedimentary habitat, which is directly influenced by CO 2 leakage, is an extremely harsh environment for many microbes, and thus harbors only specialized sedimentary acidophilic microbes. Compared with the microbial diversity at the methane-seep sediment in the Nankai Trough, very low diversity scores for 16S rRNA-tagged sequences were obtained from the CO 2 -rich sediment (Nunoura et al, 2012). These results suggest that only life forms that can physiologically adapt to high-CO 2 and low-pH conditions can survive in this environment.…”
Section: Discussionmentioning
confidence: 83%
“…Our RNA-based molecular ecological study demonstrated that the deeper sedimentary habitat, which is directly influenced by CO 2 leakage, is an extremely harsh environment for many microbes, and thus harbors only specialized sedimentary acidophilic microbes. Compared with the microbial diversity at the methane-seep sediment in the Nankai Trough, very low diversity scores for 16S rRNA-tagged sequences were obtained from the CO 2 -rich sediment (Nunoura et al, 2012). These results suggest that only life forms that can physiologically adapt to high-CO 2 and low-pH conditions can survive in this environment.…”
Section: Discussionmentioning
confidence: 83%
“…Prokaryotic SSU rRNA gene fragments were amplified with a primer set of 530F and 907R (50) from the original environmental DNA assemblages using LA Taq polymerase with GC buffer (Takara Bio) as previously described (50). For tag sequencing, primers with 10 bp of extended tag sequences in 5′-termini were used for the SSU rRNA gene amplification.…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification was performed using the Premix Ex Taq Hot Start version (TaKaRa Bio, Otsu, Japan), and the PCR mixture was prepared according to the manufacturer's instructions. For PCR amplification, the whole prokaryotic 16S rRNA gene-targeted primer pair 530F and 907R (40) was used, adhering to the PCR conditions previously described (40). PCR products were checked for size by electrophoresis on a 1.5% agarose gel using RedSafe stain (FroggaBio Inc., Toronto, Canada), purified using the MinElute gel extraction kit (Qiagen, Venlo, Netherlands), and quantified using a Quant-iT PicoGreen double-stranded DNA (dsDNA) assay kit (Life Technologies, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%